Arti Hurria and the progress in integrating the geriatric assessment into oncology: Young International Society of Geriatric Oncology review paper. Issue 2 (March 2020) - DuMontier, Clark; Sedrak, Mina S.; Soo, Wee Kheng; Kenis, Cindy; Williams, Grant R.; Haase, Kristen; Harneshaug, Magnus; Mian, Hira; Loh, Kah Poh; Rostoft, Siri; Dale, William; Cohen, Harvey Jay
Abstract: Until recently, the progress in the diagnosis and management of cancer has not been matched by similar progress in the assessment of the increasing numbers of older and more complex patients with cancer. Dr. Arti Hurria identified this gap at the outset of her career, which she dedicated toward studying the geriatric assessment (GA) as an improvement over traditional methods used in oncology to assess vulnerability in older patients with cancer. This review documents the progress of the GA and its integration into oncology. First, we detail the GA's origins in the field of geriatrics. Next, we chronicle the early rise of geriatric oncology, highlighting the calls of early thought-leaders to meet the demands of the rapidly aging cancer population. We describe Dr. Hurria's early efforts toward meeting these calls though the implementation of the GA in oncology research. We then summarize some of the seminal studies constituting the evidence base supporting GA's implementation. Finally, we lay out the evolution of cancer-focused guidelines recommending the GA, concluding with future needs to advance the next steps toward more widespread implementation in routine cancer care. Throughout, we describe Dr. Hurria's vision and its execution in driving progress of the GA in oncology, from her fellowship training to her co-authored guidelines recommending GA for all older adults with cancer—published in the year of her untimely death.